Upaya Meningkatkan Kepuasan Kerja Karyawan Bagian Fabrikasi PT XWY Melalui Lingkungan Kerja Fisik dan Disiplin Kerja - Putri, Krisni Pratama; Mulyana, Aam Rachmat (J-MAS (Jurnal Manajemen dan Sains), 2024)
The decline in employee satisfaction based on findings from interviews with several individuals PT Xwy employees still needs to be improved. The aim of this study is to assess how the physical work environment and adherence to work discipline impact on the perception of direct superiors on employee satisfaction partially and simultaneously. This research uses was 37 employees in the fabrication department of PT XWY. Samples were taken using purposive sampling technique. quantitative methods and questionnaires with an interval scale as data collection. This research data processing uses multiple regression analysis and hypothesis testing uses partial (t test) and simultaneous (f test). The findings indicate that there is a positive and significant partial effect on employee satisfaction. Additionally, work discipline positively and significantly influences employee job satisfaction. Meanwhile, for the simultaneous test, the physical work environment and work discipline have a significant effect on employee job satisfactionn.